2014
DOI: 10.1007/s00404-014-3609-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor size is an independent predictor of lymph node metastasis and survival in early stage endometrioid endometrial cancer

Abstract: TS was an independent predictor of lymph node metastasis and disease-specific survival in patients with EEC grossly confined to the uterus. Tumor >5 cm was a predictor of disease-specific survival but no difference in outcome was noted between tumor >2-5 cm and tumor ≤2 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 21 publications
6
38
2
Order By: Relevance
“…Given these findings, the authors have concluded that it may be reasonable to defer LND in all grade 1 tumors with less than 50% MMI, irrespective of tumor size. 24 Our finding of 0% rate of LN involvement in this subgroup of patients may be attributed to the limited number of patients (n =120) in our study when compared with those of Mahdi et al 23 and Vargas et al 24 (ns =1914 and 3816, respectively). We showed that only 1 of 120 women in this subgroup had LVSI, whereas no information is available about LVSI in those studies that analyzed SEER data.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Given these findings, the authors have concluded that it may be reasonable to defer LND in all grade 1 tumors with less than 50% MMI, irrespective of tumor size. 24 Our finding of 0% rate of LN involvement in this subgroup of patients may be attributed to the limited number of patients (n =120) in our study when compared with those of Mahdi et al 23 and Vargas et al 24 (ns =1914 and 3816, respectively). We showed that only 1 of 120 women in this subgroup had LVSI, whereas no information is available about LVSI in those studies that analyzed SEER data.…”
Section: Discussioncontrasting
confidence: 53%
“…In a Surveillance, Epidemiology, and End Results (SEER) data analysis, Mahdi et al 23 23 The rate of LN involvement has been reported to be 1.46% (28/1914) in this subgroup of patients. However, no information was given about LVSI in that study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…With regards to this study, we identified that this relationship also stands for grade 1 carcinomas with less than 50% invasion of the myometrium. In a similar study, Mahdi et al 25 reported that tumors larger than 5 cm had a greater possibility to present with nodal disease in carcinomas of any grade and stage. These results are closer to the ones of our study in which the greatest relationship between tumor size and nodal diseaseValthough not totally statistically importantVwas when the comparison was made between tumors larger than 4 cm and tumors measuring 4 cm or smaller.…”
Section: After the Recommendations Developed By Experts At The Esmo-ementioning
confidence: 81%
“…According to the Surveillance, Epidemiology and End Results (SEER) data, low-risk EC patients represent approximately 61% of endometrioid ECs grossly confined to the uterus [22,23]. Although the recurrence rate is very low in this subgroup of patients (1-7%), the absolute number of recurrences in low-risk EC seems to be actually considerable as approximately 70% of women with EC are given a diagnosis while the disease is confined to the uterus [24].…”
Section: Discussionmentioning
confidence: 99%